ENHANCING LIFE SKILL AT ISLAMIC BOARDING SCHOOL: AN ANALYSIS OF HIDROPONIC IMPLEMENTATION (International Conference on Social and Islamic Studies, 2022)
Santri or Islamic boarding school student must be guided so they have skill as part of life skills.one of the efforts that can be made to emprove personal skills is farming activities. However, the students’ interest in farming is still low due to the students’perceptions to being dirty and time-consuming. Therefore, it is needed to research alternative farming using the hydroponic as a soilless planting system as an effort to increase the interest in farming of the students. This literature study aims to know the interest of the students in farming by using hydroponic technology, especially students of Islamic boarding school or pesantren. It was qualitative descriptive research design with a literature review approach. The databases used in this literature study were Pro-quest, Sciencedirect, Researchgate, and Google Scoolar. It was found 218 articles from the database. After the process of identification, screening, and eligbility processes were carried out, five articles were obtained based on inclusion and exclusion criteria as well as the research objective. It can conclude that hydroponic technology increased the interest in farming of islamic boarding school student. The interest of the student indicated by a feeling of pleasure, attention, involvement, and interest in hydroponic farming.